IDENTITAS HIBRIDA PERFORMATIF PADA PERTUNJUKAN WAYANG POTEHI DI JAWA TIMUR: KAJIAN SOSIOANTROPOLOGI SASTRA - Laras Sang Dyah Pitaloka; Ririe Rengganis; Resdianto Permata Raharjo (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Wayang Potehi is a traditional Chinese puppet performance art that has developed in East Java and undergone various social, cultural, and political dynamics, resulting in the formation of a new identity. This study aims to analyze the process of cultural acculturation between Chinese and Javanese cultures, as well as the forms of cultural politics that have shaped the performative hybrid identity of Wayang Potehi performances in East Java. This research employed a qualitative approach using a socio-anthropological literary perspective. Data were collected through participant observation, in-depth interviews with sehu (puppet masters), performing artists, community leaders, and document and performance script analysis. Data were analyzed inductively through data reduction, data presentation, and conclusion drawing, while source triangulation was employed to ensure data validity. The findings reveal that the acculturation process occurs through cultural hybridity and adaptive dynamics, as reflected in the involvement of Javanese sehu, the use of multilingual languages, changes in performance contexts, and the incorporation of local legends into the performances. The cultural politics of Wayang Potehi are represented through cultural dominance, hidden transcript practices, identity negotiation, and social acceptance, which collectively give rise to a new performative hybrid identity.